COMPARATIVE OUTCOMES AND PARAMETERS OF DRAINING SETON VERSUS FISTULOTOMY IN TREATING ANAL FISTULAS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Anal fistula is a common anorectal condition associated with significant morbidity and recurrence. Draining seton placement and fistulotomy are widely used surgical treatment options, but their comparative outcomes remain a subject of clinical interest. Aim: To compare the clinical outcomes and parameters of draining seton and fistulotomy in the management of anal fistulas. Materials and Methods: This prospective comparative observational study was conducted in the Department of General Surgery of a tertiary care hospital in Mumbai over a period of 12 months. A total of 40 patients diagnosed with anal fistula were included, with 20 patients each undergoing draining seton placement and fistulotomy. Baseline demographic characteristics, fistula type, postoperative pain, wound infection, recurrence, and reintervention rates were evaluated and compared between the two groups. Results: The mean age was comparable between the draining seton and fistulotomy groups (37.10 ± 9.48 vs. 35.25 ± 12.06 years; p=0.59). Postoperative pain scores and wound infection rates showed no significant differences between groups (p>0.05). Recurrence was significantly higher in the draining seton group than in the fistulotomy group (40.0% vs. 5.0%; p=0.008). Similarly, reintervention was required more frequently following draining seton placement (65.0% vs. 30.0%; p=0.027). Conclusion: Both procedures demonstrated acceptable safety profiles; however, fistulotomy was associated with lower recurrence and reintervention rates. Fistulotomy appears to provide superior long-term outcomes in appropriately selected patients, while draining seton remains a useful sphincter-preserving option for selected complex fistulas.